Australian and New Zealand national evidence‐based recommendations for the investigation and follow‐up of undifferentiated peripheral inflammatory arthritis: an integration of systematic literature research and rheumatological expert opinion. (16th October 2013) - Barrett, Claire; Bird, Paul; Major, Gabor; Romas, Evange; Portek, Ian; Taylor, Andrew; Zochling, Jane
Abstract: Aim: To develop Australian and New Zealand (ANZ) recommendations for the investigation and follow‐up of undifferentiated peripheral inflammatory arthritis (UPIA) using an evidence‐based approach. Methods: Ten questions pertaining to the investigation and follow‐up of patients with UPIA in daily rheumatological practice were defined by clinicians using a modified Delphi approach. A systematic literature search was conducted for each of the final questions. The results were presented to a workshop of 54 ANZ rheumatologists in May 2009. Discussions were held to develop consensus statements for each question, based on published evidence and clinical experience/expertise. Results: Ten recommendations were made on diagnostic value of clinical features in the patient's history and examination, predictors of poor prognosis and persistence, synovial fluid analysis, serology, imaging and human leukocyte antigen B27 testing. The lack of specific research to inform recommendations presented a challenge. Dynamic discussion groups outlined individual experience in areas without good quality clinical trial evidence. The median strength of support for the final set of recommendations was 7/10 (interquartile range 6–8), ranging from 6 to 9 for individual statements. Conclusion: Ten ANZ recommendations for the investigation and follow‐up of UPIA were formulated, based on available evidence and extensive clinical experience. The systematic literature review was of limited value while animated discussion of individual experience, with subsequent information exchange, highlighted the importance of merging clinical expertise with published literature to establish practical recommendations that can improve quality of care in rheumatology.